Study of Perceived Organizational Support and Work Engagement on Job Satisfaction - Tri Endi Ardiansyah PS; Nursimah Dara; Ilma Darojat (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
The purpose of this study is to analyse among Job Satisfaction, especially problems regarding the effect of Perceived Organizational Support and Work Engagement on Job Satisfaction. From the data collection activities, 96 respondents were obtained. Data analysis was carried out with the help of the SPSS version 26 program, the data testing technique in this study included multiple linear regression test, coefficient of determination test, t test (partial test), and F test (simultaneous test). The results showed that partially Perceived Organizational Support had a positive effect on Job Satisfaction. This is indicated by t-count higher than t-table (21,525 and 1,985), and Work Engagement has a positive effect on Job Satisfaction. This is indicated by t-count higher than t-table (13,817 and 1,985), the regression significant value of 0.000 up to 0.050. And simultaneously, Perceived Organizational Support and Work Engagement have a positive effect on Job Satisfaction, where F-count is higher than F-table (308,577 and 3.09). Result of multiple regression equation value Y = 8.104 + 0.551 X1 + 0.271 X2.